Asymptotic behavior of solutions of stochastic functional-differential equations with Poisson switchings - Gotinchan, G. I.; Yasinsky, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We obtain conditions of global asymptotic stability of solutions of stochastic functional-differential equations with Poisson switchings.